2020
DOI: 10.1007/s42242-020-00090-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bionic mechanical stimulation on the properties of engineered cartilage tissue

Abstract: Tissue-engineered cartilage (TEC) remains a potential alternative for the repair of articular cartilage defects. However, there has been a significant different between the properties of TEC and those of natural cartilage. Studies have shown that mechanical stimulation such as compressive load can help regulate matrix remodelling in TEC, thus affecting its biomechanical properties. However, the influences of shear induced from the tissue fluid phase have not been well studied and may play an important role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The scaffold was prepared by SLS and is shown in Figure (a–c), which had good flexibility. The pore size of the scaffold ranges from 320 to 800 μm, which was reported to be appropriate for cell growth. The Cu 2+ release kinetics of the PPDO/Cu@ZIF-8 scaffold is shown in Figure d. Visibly, the scaffold released a large amount of Cu 2+ on the first day (410.788 μg/L).…”
Section: Resultsmentioning
confidence: 98%
“…The scaffold was prepared by SLS and is shown in Figure (a–c), which had good flexibility. The pore size of the scaffold ranges from 320 to 800 μm, which was reported to be appropriate for cell growth. The Cu 2+ release kinetics of the PPDO/Cu@ZIF-8 scaffold is shown in Figure d. Visibly, the scaffold released a large amount of Cu 2+ on the first day (410.788 μg/L).…”
Section: Resultsmentioning
confidence: 98%
“…Meanwhile, CTCs in groups 3 and 4 exhibited significantly enhanced protein expression after 3 days of cyclic stretching culture (Figure ). In many studies, mechanical stimulation has been shown to induce specific differentiation of primary cells. , For example, Czaplewski et al conducted the periodic tensile test on PLA-/PCL-woven scaffolds, which demonstrated that periodic stretching significantly upregulated the expression of tendon markers and inhibited osteoblastic differentiation . Chen et al performed cyclic stress experiments on woven silk/collagen scaffolds and found that MSCs derived from human embryonic stem cells expressed tendon-related proteins and genes under mechanical stimulation .…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of the dedifferentiated chondrocytes changes from triangle to the elongated spindle, with the main collagen changing from type-II to type-I [ 44 ]. The occurrence of COL I, as the main collagen protein of fibrous cartilage, indicates poor quality of the cartilage, which is prone to degenerate and unable to fulfill its function [ 45 , 46 ]. However, the main type of collagen in fibrocartilage such as articular disc and condyle is COL I. Magnesium may promote the regeneration of fibrocartilage by promoting the production of COL I, so it may also be used for condylar cartilage and articular disc regeneration [ 47 ].…”
Section: Discussionmentioning
confidence: 99%